Fuyūzulbārī fī sharḥ Ṣaḥīḥ al-Buḵẖārī - Rizvi, Sayyid Mahmud Ahmad, 1924- (Maktabah-yi Ri̤zvān, 1977)
Commentary on Ṣaḥīḥ al-Bukhārī, one of the six authentic compilations of Hadith (Islamic traditions) compiled by Muḥammad ibn Ismāʻīl al-Bukhārī, 810-1870.